Evaluation of Speeding and Behaviour of Drivers in Roadwork Zones - Donatas Čygas; Dovydas Skrodenis; Aivaras Paškauskas; Živilė Sušinskaitė; Laura Žalimienė (The Baltic Journal of Road and Bridge Engineering)
Due to the increased traffic flow, more and more roadwork zones are formed in highways. Accidents are a significant problem in all European countries in roadwork zones while noncompliance with speed limits is one of the major safety concerns. Therefore roadwork zones are critical places from the point of traffic safety view where the possibility to get into an accident is increased. Roadwork zones introduce deviations from regular travel situations, and appropriate speed is needed to assure that the driver navigates safely through the roadwork zone. This research focuses on speed measurement in road work zones and attempts to evaluate the effectiveness of safety measures on speed limit compliance.